GEOCHEMISTRY AND GEOCHRONOLOGY OF THE MESOZOIC VOLCANIC ROCKS IN THE SOUTHERN GREAT XINGGAN RANGE, NE CHINA - Huaimin Xue (Геодинамика и тектонофизика, 2017)
Mesozoic volcanic rocks are widespread throughout the Great Xing’an range, NE China. Their ages formed from about 180 Ma to 120 Ma, with a strong peak about 125 Ma, and several weak peaks at ∼116 Ma, ∼140 Ma and ∼156 Ma respectively in age histogram. These complicated age spectrum points out that the volcanism may be related not only with the subduction of the Pacific plate, but also with closure of the Okhotsk ocean.